A Literatur Review Do Not Resuscitate: An Ethical Dilemma in Nursing Practice - Dewi, Ni Made Ratih Comala; Aryana, I Gusti Ngurah; Bela, I Kadek Miki Indra; Widiastuti, Ni Kadek Nefi; Wahyuni, Ni Wayan Sri; Wulandari, Ida Ayu Putri (Babali Publisher, 2024)
Introduction: Medical interventions for pulmonary heart resuscitation in patients with DNR raise a conflict situation among nurses, where faced with two equally unsatisfactory decisions that are contrary to ethical principles. The practical approach that can be taken is to build patient and family confidence, define their goals, and apply ethical principles of autonomy: beneficence, nonmaleficence, and justice. This research aims to find out the ethical dilemma of DNR in nursing practice. Methods: A literature review was conducted using three journal databases: ScienceDirect, PubMed, and Google Scholar. Kata kunci dalam tinjauan pustaka ini disesuaikan dengan Medical Subject Heading (MeSH) yang terdiri dari “ethic” AND “principle based” AND “do not resuscitate” AND “nursing ethic”. Several inclusion criteria were set to obtain eligible articles: published between 2014 and 2023, and written in English or Bahasa. Fifteen eligible articles were finally included in the analysis. Results: Four subthemes were found: factors that influence DNR decisions, knowledge and understanding of health professionals related to DNR, ethical dilemmas, and care of DNR patients. Conclusion: The DNR decision requires ethical competence based on DNR information and understanding. The DNR decisions are based on the principles of autonomy, beneficence, nonmaleficence, and justice. The role of a nurse tends to be psychosocial intervention.